Philosophy history and problems - Stumpf, Samuel Enoch 1918- (McGraw-Hill, 2003)
Bringing together "Socrates To Sarte And Beyond, Seventh Edition" and "Philosophical Problems, Fifth Edition", this text offers an accessible historical survey of philosophical ideas